The shaman's wages: trading in ritual on Cheju Island - Yun, Kyoim (Korean studies of the Henry M. Jackson School of International Studies, 2019)
A neo-Confucian reformer's 1702 purge -- Cultural politics of Cheju shamanism in the twentieth century -- The art of ritual exchange -- Skillful performer or avaricious animator? -- A Kut as heritage goods with the UNESCO brand.